MICROFACIES TYPES AND PALEONTOLOGICAL CHARACTERISTICS OF THE VISEAN CARBONATE ROCKS (THE SOUTHERN ZONE OF DNIEPER-DONETS BASIN) - Liashchova, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Foraminifera and microfacies of the Visean carbonate rocks of the Southern zone Dnieper-Donets basin are studied. Microscopy study of carbonate rocks allowed us to establish their mineral composition, textural and structural features, the degree and nature of the secondary changes and to describe the main microfacies. The Visean carbonate rocks are represented by the following microfacies types: bioclastic, foraminiferal, foraminifera-algal, algal, microbial (peloidal), aggregate-grain (grapestones) grainstones; bioclastic, foraminiferal, algal, foraminifera-algal, crinoidal packstone and wackstone. The study of faunal debries and algal flora combined with a microfacies analysis allowed us to approach the reconstruction of carbonate sedimentation conditions. Biota and microfacies of the studied carbonate rocks indicate the presence of four facies zones (FZ). These are FZ 2 deep shelf, FZ 6 platform-margin shoals, FZ 7 platform interior-normal marine and FZ 8 platform interior – restricted. The standard microfacies types (SMF) are represented by SMF 8-9 (bioclastic wackestone), SMF 10 (bioclastic packstone), SMF 16 (microbial (peloid) grainstone), SMF 17 (аggregate-grain (grapestone) grainstone), SMF 18 (bioclastic grainstone and packstone with abundant and rock-building benthic foraminifera or calcareous green algae). This shows that the studied rocks were deposited in a carbonate platform zone and its slopes. Stagnant areas with limited water circulation are locally occurred.